Compaction Characteristics of Cold Recycled Mixtures with Asphalt Emulsion and Their Influencing Factors - Wang, Decai; Yao, Hui; Yue, Jinchao; Hu, Shengneng; Liu, Junfu; Xu, Mei; Chen, Siyu (Frontiers in Materials, 2021)
The objective of this study is to investigate the compaction characteristics of cold recycled mixtures with asphalt emulsion (CRME) using the Superpave gyratory compactor (SGC) method. Five characteristic parameters were proposed and calculated including the compaction energy index, the compaction energy index, three compaction energy indicators at different compaction stages. The influence of these parameters and material compositions were analyzed for the pavement performance. The difference between SGC and Marshall double-sided compaction/heavy compaction method was compared. The results show that the proposed parameters can better reflect the compaction characteristics of CRME, and the mixture effect with SGC of 50 gyrations was close to that with 75 blows using the Marshall compaction. The asphalt emulsion contents and compaction temperatures had a significant effect on compaction characteristics, but the effect of aggregate gradations was not significant. The appropriate asphalt emulsion and the new aggregate content can increase the capability of the CRME to resist the permanent deformation. The optimum mixing water content of CRME obtained by the SGC method was reduced by 18%, but the density increased by 3.5%, compared with the heavy compaction method. Finally, a new idea to determine the optimum emulsified asphalt content of CRME was provided through analyzing the compaction characteristic parameters.